Gender differences in the Italian academic landscape: Examining inequalities within the medical area in the last decade - Roberta Magnano San Lio; Mara Morini; Enrico Di Rosa; Alessandra Sinopoli; Virginia Casigliani; Manuela Martella; Andrea Maugeri; Martina Barchitta; Maria Carmela Agodi; Ilenia Picardi; Antonella Agodi (PLoS ONE, 2025)
Gender equality remains a key focus in research and innovation policies. However, the academic sector still exhibits significant under-representation of women in leadership roles and horizontal segregation affecting career trajectories. This study examines gender inequalities in top positions and career progression within Italy’s Medical Sciences sector (Area 06) from 2014 to 2023, through data from the Cineca portal, including details on academic roles, gender, region, and scientific-disciplinary sectors (SSDs). Gender disparity was evaluated using the Glass Ceiling Index (GCI) and the Glass Door Index (GDI). Data analysis up to 2023 shows a gender inversion in career progression: women dominate early career stages – accounted for 71.5% of research fellows and 57.1% of RTDA positions –, but men prevail in senior roles, with 61.8% associate professors and 71.8% full professors. This trend is consistent across most SSDs. Although temporal analysis indicates a reduction in gender disparities in top positions – with a GCI ranging from 2.3 in 2015 to 1.7 in 2023 – GCI values above one across all regions suggest persistent gender inequality. The GDI values, ranging from 1.3 in 2015 to 1.6 in 2023, exhibit considerable variability; however, overall, the disparities have worsened by 2023. These findings underscore the need for concrete measures to enhance equity and inclusivity in academia. Developing and implementing initiatives, programs, and policies that guarantee equal opportunities and resources for all researchers, irrespective of gender, is essential.